INOCULATION ENHANCES SOYBEAN PHYSIOLOGY AND YIELD UNDER MODERATE DROUGHT - Basal, Oqba; Szabó, András (LIFE: International Journal of Health and Life-Sciences, 2019)
With a high seed content of protein and oil, soybean is one of the most widely-grown legumes worldwide. Inoculation process enables soybean to achieve most, and sometimes all, of his nitrogen requirements through N2-fixation process, however, this process, like soybean plant itself, is drought-sensitive. Drought is globally-increasingly imposed as a result of climatic changes, negatively affecting soybean production. An experiment was conducted in Debrecen, Hungary in 2017 and 2018 to evaluate the influence of moderate drought stress on some physiological parameters of both inoculated and non-inoculated soybean plants. Results showed that drought negatively affected soybean’s physiology and yield, regardless of inoculation; however, inoculated plants could maintain better values of studied parameters relative to their non-inoculated counterparts. On the other hand, drought occurring during R4 stage had more noticeable effects on soybean plants as compared to drought occurring earlier (at V2 stage) during vegetative period. It was concluded that inoculation could be a beneficial strategy in order for soybean to reveal better physiology and, consequently, better yield under moderate drought conditions, and that the timing of drought stress occurrence is crucial regarding soybean’s vigor and final seed yield.